Answer:
A is 3 B is 4 and C is 2
Step-by-step explanation:
this is most likely right unless your usong a diffrent formula
The constant in an algebraic expression is the only term that cannot be changed.
Terms with variables are not constants as their values can changed as the variables change.
Our equation is 3m+7
M is a variable. Therefore the term '3m' is not the constant.
This leaves us with the term '7'. There is no variable present in this term.
'7' is the constant in this equation.
I believe its 1.8
hope this helps :)
Answer:
-5
Step-by-step explanation:
First, distribute the 2 to the 3, -9, and 5. You will get 6 + 6 - 18 + 10 + (-9). Then, you can start from the beginning and work through combining the terms. The original equation is in bold after every step.
6 + 6 - 18 + 10 + (-9)
6+6 = 12
12 - 18 + 10 + (-9)
12-18 = -6
- 6 + 10 + (-9)
-6 + 10 = 4
4 + (-9)
4 - 9 = -5
Answer: -5
(4 – 2i)(6 + 2i)
FOIL
First : 4*6 =24
Outer: 4*2i = 8i
Inner: -2i* 6 = -12i
Last: -2i*2i = -4i^2 =-4(-1) =4
Add together
24+8i-12i+4
28-4i
Answer: 28-4i